2016
DOI: 10.1128/aac.01696-16
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antiedematous and Protective Effects of Ciprofloxacin in Pulmonary Ricinosis

Abstract: The plant toxin ricin is considered a biological threat agent of concern and is most toxic when inhaled. Pulmonary exposure to a lethal dose of ricin can be redressed by treatment with antiricin antibodies; however, late antitoxin intervention is of limited efficacy. This limitation is associated with overt lung damage, clinically manifested as severe pulmonary inflammation, which develops over time. Increased evidence indicates that ciprofloxacin, a broad-spectrum antimicrobial agent, possesses immunomodulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…We would like to point out in this context that since this study was performed with outbred mice, employing an adoptive transfer approach to prove unequivocally the role of the neutrophils in promotion of toxicity is not possible. Understandably, TBI is not an applicable clinical countermeasure against ricin intoxication, however, the results obtained in this work strongly strengthen our findings from the past, indicating that attenuation of inflammation is critical for optimal treatment of pulmonary ricinosis, especially if antibody-based treatment begins at late time points following intoxication [ 11 , 14 ]. Furthermore, the present study strongly suggests that clinical approaches aimed to attenuate neutrophil-mediated damage could be implemented in the future in the development of an effective anti-ricin medical countermeasure.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We would like to point out in this context that since this study was performed with outbred mice, employing an adoptive transfer approach to prove unequivocally the role of the neutrophils in promotion of toxicity is not possible. Understandably, TBI is not an applicable clinical countermeasure against ricin intoxication, however, the results obtained in this work strongly strengthen our findings from the past, indicating that attenuation of inflammation is critical for optimal treatment of pulmonary ricinosis, especially if antibody-based treatment begins at late time points following intoxication [ 11 , 14 ]. Furthermore, the present study strongly suggests that clinical approaches aimed to attenuate neutrophil-mediated damage could be implemented in the future in the development of an effective anti-ricin medical countermeasure.…”
Section: Discussionsupporting
confidence: 54%
“…Pulmonary ricin intoxication is characterized by a confined lung pathology associated with cytokine storm, massive neutrophil infiltration, and ultimately, severe edema formation, leading to respiratory failure and death. Neutrophils are considered a major hallmark of ricin- [ 11 , 14 , 16 ], as well as non-ricin- [ 19 , 20 , 22 , 23 ] mediated lung injuries, where aggressive or prolonged neutrophil responses result in deleterious inflammatory conditions and tissue destruction, while on the other hand, decreased pulmonary neutrophil infiltration is associated with attenuation of injury severity [ 18 , 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this finding, the levels of the serum-resident enzyme cholinesterase, as well as total protein, are increased significantly in the BALF of intoxicated mice, indicating that the blood-lung barrier is severely impaired. Increased Evans Blue dye extravasation, as a marker for increased vascular permeability, has also been reported [ 12 , 39 ].…”
Section: Ricin-induced Cytotoxicity and Pathophysiology Of Pulmonamentioning
confidence: 99%
“…Recent data suggests that small-molecule compounds that either interfere with or inhibit the intracellular trafficking of ricin may also be beneficial against ricinosis [ 7 , 8 , 9 , 10 ]. Another approach has recently shown that the co-administration of antitoxin antibodies with immunomodulatory drugs enables toxin neutralization while decreasing lung injury severity, thus improving treatment outcomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%